Efficacy and safety of panitumumab alone or in association with radiotherapy in unresectable cutaneous squamous cell carcinoma. (24th August 2020) - Hourbeigt, K.; Ehret, M.; Visseaux, L.; Durlach, A.; Petit, A.; Sanchez, J.; Grange‐Prunier, A.; Barbe, C.; Servagi‐Vernat, S.; Grange, F.
Abstract: Background: The prognosis of unresectable cutaneous squamous cell carcinomas is very poor. Objective: To evaluate the efficacy and safety of panitumumab alone or in association with radiotherapy in the treatment of unresectable cutaneous squamous cell carcinoma. Methods: This was a monocentre retrospective study of all consecutive patients having received at least two courses of panitumumab, alone or in association with radiotherapy, between 2016 and 2019. The primary endpoint was the rate of best overall response, evaluated according to the RECIST 1.1 criteria. The secondary endpoints were the response and disease control rates at 6 weeks and 6 months, progression‐free survival, overall survival and safety. Results: A total of 25 patients were included; their median age was 86 years, and 17 (86%) had a WHO performance status over 2. The best overall response rate was 52%, including four complete responses (16%) and nine partial responses (36%). All patients with complete response and five out of nine patients with partial response had received concurrent radiotherapy, in most cases in moderate to low doses (<40 Gray, 67%). The response rates at 6 weeks and 6 months were 12% and 28%, respectively. The control rates at 6 weeks and 6 months were 84% and 32%, respectively. Median progression‐free survival was 6.9 months, and median overall survival was 10.5 months. Grade 3 side‐effects, mostly dermatological, occurred in 16 patients (64%). Conclusion: These results suggest that panitumumab remains pertinent in the treatment of unresectable cutaneous squamous cell carcinoma, in particular in association with radiotherapy, despite recent advances with anti‐PD‐1 antibodies. It presents several advantages: it can be used in very elderly or feeble patients, it does not provoke anaphylactic or other irreversible or life‐threatening side‐effects, and our study observed some long‐term responses. Further prospective investigation of anti‐EGFR antibodies, in association with anti‐PD‐1 antibodies and/or chemotherapy, should be conducted.